Building Coalitions: Coalition Facilitator Guide - Charles H. Bell; Penne Smith; Elizabeth B. Bolton; Lisa Guion (EDIS, 2002)
This document is FY494, Part 2 of the 16 part series adapted for use in Florida by Elizabeth B. Bolton and Lisa Guion. Reprinted with permission March, 1997. Revised April, 2002.